Korelasi antara bobot badan induk dengan litter size, bobot lahir dan mortalitas anak kelinci New Zealand White - Sismala Widitania; Yon Soepri Ondho; C. M. Sri Lestari (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
This study aims to determine the relationship between body weight of does with litter size, birth weight and mortality in New Zealand White (NZW) rabbits. The research was conducted at the Central Breeding and Raising Non Ruminant Livestock unit Balekambang, Surakarta, Central Java. The material used in this study was 35 does that had sexual maturity and have given birth at least once aged maximum 3 years old. In addition, the study also used 7 bucks aged approximately 2 years. Data were analysed using simple linear regression analysis. The study found that the weight of the does had a very weak correlation value to litter size, birth weight and mortality of young rabbits. Keywords: Rabbits, New Zealand White, body weight, litter size